TINDAKAN PEMERINTAH INDONESIA DALAM MERESPON PERUBAHAN KUOTA HAJI ARAB SAUDI TERHADAP JAMA’AH HAJI INDONESIA - Syahidah Fadla; Mhd. Saeri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
ABSTRACT The policy of the Government of Saudi Arabia in determining the number of quotas for Indonesian hajj in the 2010-2018 period prompted a response from the Government of Indonesia in various ways. This is even more interesting because determining the number of haj quotas will add to the length of the waiting list for Indonesian pilgrims and will occupy the longest waiting list in the world. This research shows the various actions and efforts of the Government of Indonesia in responding to the hajj quota. Actions and efforts made starting from the proposal to revise the provisions of the Organization of Islamic Cooperation (OIC) in 1978 regarding the Hajj quota of 1:1000 of the total Muslim population in each country, increasing the quota through bilateral relations between the two countries either through the Ministry of Religion of the Republic of Indonesia, the Indonesian Parliament and the President Indonesia as well as the transfer of the remaining quota from various countries such as the Philippines, Singapore, Japan, Timor Leste, Thailand and Cambodia. With Indonesia's active participation in the OIC, it is hoped that it will be able to convince the Government of Saudi Arabia to provide an additional quota of up to 250 million to Indonesian pilgrims from the remaining haj quota from countries that are not fulfilled. Keywords: Hajj Quota, Indonesian Government's Response.